2019
DOI: 10.1155/2019/8485031
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Heavy Metal Dynamics in a River‐Lagoon System

Abstract: This paper describes the development of a two-dimensional water quality model that solves hydrodynamic equations tied to transport equations with reactions mechanisms inherent in the processes. This enables us to perform an accurate assessment of the pollution in a coastal ecosystem. The model was developed with data drawn from the ecosystem found in Mexico’s southeast state of Tabasco. The coastal ecosystem consists of the interaction of El Yucateco lagoon with Chicozapote and Tonalá rivers that connect the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Previous studies have also reported good fits for measured data for Cd in river water (Wu et al, 2005;Wu, 2008;Kashefipour and Roshanfekr, 2012). In a related study, Torres-Bejarano et al (2019) reported high prediction of Cd, Pb, and Ni in river water using two-dimensional water quality model they developed numerically.…”
Section: Heavy Metal-regression Models and Longitudinal Dispersion Comentioning
confidence: 99%
“…Previous studies have also reported good fits for measured data for Cd in river water (Wu et al, 2005;Wu, 2008;Kashefipour and Roshanfekr, 2012). In a related study, Torres-Bejarano et al (2019) reported high prediction of Cd, Pb, and Ni in river water using two-dimensional water quality model they developed numerically.…”
Section: Heavy Metal-regression Models and Longitudinal Dispersion Comentioning
confidence: 99%
“…Barrios-Piña et al [68] used the code to probe a new turbulence model for flow through vegetation. On the other side, Torres-Bejarano et al [69] recently used it to assess pollution distribution in an estuarine ecosystem. Turbulence models attached to the hydrodynamic model were tested by Rodriguez-Cuevas et al [70], where several turbulence models were coded to predict wakes around conic islands, and the results showed good agreement with the measurements experiments.…”
Section: Appendix B Numerical Solution Strategymentioning
confidence: 99%
“…In this work, we performed an assessment of the flooding risk of Tamuín city, through a parallel self-made hydrodynamic model previously validated in diverse studies [66][67][68][69][70] and carefully calibrated with field measurements, with the idea of having full control of processes, methods and precision provided by owning the code. Streamflow of Tampaón River in wet and dry seasons was simulated according to historical records.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that some other models have been created specifically for research purposes. Examples include numerical modeling of heavy metals 4 , research on water flows through vegetation 5 , research on turbulence models 6 , fresh water plumes 7,8 in river-sea interaction 9 , and numerical assessment of flood risk 10 . The ability to introduce toxic wastes to waters without negatively affecting human health or ecosystems is known as assimilation capacity, and it is one of many practical and affordable dissolved for water quality management.…”
Section: Introductionmentioning
confidence: 99%